Study of Morphometric Characteristics of Freshwater Putul, Botia lohachata in Kompo River of Bagmara, Rajshahi, Bangladesh - Joadder, Md Abdur Razzaq; Siraz, Rabia Binta; Roy, Susen; Jahan, Syeda Nusrat; Khanom, Dil Afroza; Sarker, Md Al-Amin (Journal of Science Foundation, 2020)
This study described about the morphometric characteristics of Botia lohachata, collected from the Kompo River at Rajshahi , were studied for a period of four months from July to October 2014. Length frequency distributions, length-length relationships, length-weight relationship, sex ratio, Fulton's condition factor and fecundity of B. lohachata were studied in the present study. This is the maiden research conducted on B. lohachata in Bangladesh. The highest mean total lengths were 61.16±4.77 mm (combined sex), 63.80±4.79mm (female) and 58.17 ±3.30mm (male). Maximum 43.34% female fishes were belonging to the length category of 61-65 mm where as 61.41% male were belonging to 56-60 mm. Similar findings are also presented for standard length, fork length, body depth, dorsal length, pectoral length, pelvic length and anal length. Linear relationships were also studied among mentioned lengths. Strong positive correlations were observed in all cases. The highest mean body weight was weight 2.67±0.71g (October) in combined sex, this value was 3.10±0.59 in female (September) and 2.25±0.38g in male (September). Strong positive correlations were also observed between total length and body weight. Observed value of sex indicated that 54% specimens were female and remaining 46% were male. The value of chi square (x2) was 2.4 at 1 degree of freedom (p<0.005) strongly indicated that the observed sex ratio not differs significantly from the expected ratio (1:1).The Fulton’s condition factors In case of combined sexes, the highest condition factor 1.156±0.126 was recorded in month of October, female highest condition factor 1.190±0.136 and male highest condition factor 1.135±0.103. Journal of Science Foundation 2019;17(1):15-33